1982
DOI: 10.1042/bj2010279
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of myofibrillar proteins by trypsin-like serine proteinases.

Abstract: The effects of the Ca2+-activated cysteine proteinase, the rat trypsin-like serine proteinase and bovine trypsin on myofibrillar proteins from rabbit skeletal muscle are compared. 2. Myofibrils that had been treated at neutral pH with the Ca2+-dependent proteinase and with the rat enzyme were (a) analyzed by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis and (b) examined in the electron microscope. Treatment with each proteinase resulted in the loss of the Z-discs, but the rat enzyme caused much mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Although, according to the reports of Kay et al. a certain intracellular serine protease mainly participates in initial degradation of myofibrillar proteins in mouse muscle, 1,2 only a few studies have been reported on intracellular serine protease in fish muscle. According to the previous studies, fish muscle serine proteases are roughly divided into two groups on the basis of the behavior of solubility in muscle homogenate.…”
Section: Effect Of Various Protease Inhibitors On the Activity Of Thmentioning
confidence: 98%
See 2 more Smart Citations
“…Although, according to the reports of Kay et al. a certain intracellular serine protease mainly participates in initial degradation of myofibrillar proteins in mouse muscle, 1,2 only a few studies have been reported on intracellular serine protease in fish muscle. According to the previous studies, fish muscle serine proteases are roughly divided into two groups on the basis of the behavior of solubility in muscle homogenate.…”
Section: Effect Of Various Protease Inhibitors On the Activity Of Thmentioning
confidence: 98%
“…These results revealed that crucian carp MBSP possesses enzyme activity in vivo . Kay et al 1,2 . suggested that endogenous serine protease mainly participates in initial degradation process of myofibrillar proteins.…”
Section: Effect Of Various Protease Inhibitors On the Activity Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…2000). Except calpains (Mykles and Skinner 1983), proteinases involved in the nonlysosomal pathway have been characterized as serine proteinases (Kay et al. 1982a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of myofibrils and mitochondria as well as other sarcoplasmic organelles reportedly occurs in different ways [9]. Degradation of myofibrilar structures is probably a two-step process: first they are destroyed by neutral and basic proteases [11,12] and then their residues are utilized by lysosomal enzymes [10]. Lysosomes alone accomplish the destruction of mitochondria [14].…”
Section: Resultsmentioning
confidence: 99%